Naucnaja rabota CPbGUFKe im. P. F. Lesgafta: Stanovlenie, sostojanie i perspektivy - Gorelov, A. A.; Askinazi, S. M. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
Modern research activity at university - logical continuation of ideas and the traditions incorporated by the founder of this high school - P.F. Lesshaft, his pupils, followers and adherents. And one of its basic principles is the princi-ple of unity of educational and scientific work.